THE INTERNATIONAL CRIMINAL JUSTICE MECHANISMS: SIERRA LEONE’S POST-CONFLICT ACCOUNTABILITY - Thomas Sheku Marah (Journal of Governance and Public Administration, 2025)
Sierra Leone’s brutal civil war (1991–2002) bequeathed a dark history of mass atrocities, war crimes, crimes against humanity, and systematic gender-based violence. Therefore, the Special Court for Sierra Leone (SCSL) was created in 2002 as a hybrid international court to try the perpetrators responsible for these crimes. This research examines the framework, jurisdiction, and achievements of the SCSL as a post-conflict accountability and justice-delivering court. This study aims to critically assess the contribution of the SCSL to transitional justice by examining the prosecution of high-level perpetrators, the response of the SCSL to sexual and gender-based violence, the strengthening of community outreach through outreach programs, and the nation-building of local judiciaries. Using a qualitative approach based on case study methods, the study examines five central aspects of SCSL activity. The evidence was generated from primary sources such as court judgments, government reports, and policy reports, as well as from secondary literature: NGO reports, academic literature, and human rights reports. The cross-cutting themes and the impact—on legal, political, and social levels—of the tribunal were assessed through thematic analysis. The SCSL has set important new precedents in international law, such as the prosecution of a sitting head of state and the recognition of sexual violence as a distinct war crime. Its outreach and capacity-building programs served to promote legal literacy and institutional capacity in Sierra Leone, notwithstanding limitations with respect to funding, outreach to rural areas, and sustainability. The article argues that hybrid tribunals like the SCSL may be instructive for future post-conflict systems of justice insofar as they achieve a balance between international legal imperatives and local affinity.